Fade as Cultural Capital: A Case Study of Young Men’s Culture in a Barbershop in Amsterdam - Ramkishun, Rayn (Komunitas: International Journal of Indonesian Society and Culture, 2024)
Fade haircuts are one of the most popular looks these days. The haircut entails cutting the sides and the back of the head as short as possible and making it transition or "fade" into the longer hair on the head. This article looks at the shared culture of men in a barbershop in Amsterdam Nieuw-West through the theory of cultural capital by Bourdieu. This theory, used to analyze the upper-class French, can be implemented to analyze all kinds of groups and people. Manners, knowledge, behaviors, and skills that a person can tap into to demonstrate one's cultural competence and social status all come together in cultural capital. These beforenamed components are a necessity to be part of the urban middle-class culture.